Optimizing Antiviral Dosing for HSV and CMV Treatment in Immunocompromised Patients - Daan W. Huntjens; Jacob A. Dijkstra; Lisanne N. Verwiel; Mirjam Slijkhuis; Paul Elbers; Matthijs R. A. Welkers; Agnes I. Veldkamp; Marianne A. Kuijvenhoven; David C. de Leeuw; Heshu Abdullah-Koolmees; Maria T. Kuipers; Imke H. Bartelink (MDPI AG, 2023)
Herpes simplex virus (HSV) and cytomegalovirus (CMV) are DNA viruses that are common among humans. Severely immunocompromised patients are at increased risk of developing HSV or CMV disease due to a weakened immune system. Antiviral therapy can be challenging because these drugs have a narrow therapeutic window and show significant pharmacokinetic variability. Above that, immunocompromised patients have various comorbidities like impaired renal function and are exposed to polypharmacy. This scoping review discusses the current pharmacokinetic (PK) and pharmacodynamic (PD) knowledge of antiviral drugs for HSV and CMV treatment in immunocompromised patients. HSV and CMV treatment guidelines are discussed, and multiple treatment interventions are proposed: early detection of drug resistance; optimization of dose to target concentration by therapeutic drug monitoring (TDM) of nucleoside analogs; the introduction of new antiviral drugs; alternation between compounds with different toxicity profiles; and combinations of synergistic antiviral drugs. This research will also serve as guidance for future research, which should focus on prospective evaluation of the benefit of each of these interventions in randomized controlled trials.